When does policy learning lead to policy change? Exploring the causal chain from learning to change - Sandra Plümer (International Review of Public Policy)
Policy learning is a crucial mechanism for policy change. Yet, there is still uncertainty about the conditions under which learning actually leads to change. This article clarifies the causal chain from policy learning to policy change in two steps. First, it develops a so-called “Learning Product Framework” which distinguishes three central features of learning products: policy belief change, policy preference change, and policy output change. Second, it presents a “Typology of Causal Pathways between Learning and Change”, leading to four different learning-induced policy changes. In the first pathway, policy beliefs have changed, but preferences and outputs remain unchanged, resulting in policy stability rather than policy change. In the second pathway, policy beliefs and preferences have changed, but the output has not been altered, also leading to policy stability. In the third pathway, beliefs, preferences, and outputs have changed, but they are not aligned, resulting in “Non-Congruent Policy Change”. Only in the fourth pathway are all three features aligned and fulfilled, leading to “Congruent Policy Change”. This conceptual clarification confirms previous findings that policy learning alone is not sufficient for policy change. It demonstrates the combination of cognitive, behavioral, and social mechanisms needed for learning-induced policy change.